Safety and sedative effect of intranasal dexmedetomidine in mandibular third molar surgery: a systematic review and meta-analysis - Liu S; Wang Y; Zhu Y; Yu T; Zhao H (Dove Medical Press, 2019)
Shaopeng Liu,1,2,* Ye Wang,1,2,* Yong Zhu,1,2 Tingting Yu,3 Huaqiang Zhao1,2 1Shandong Provincial Key Laboratory of Oral Tissue Regeneration, School of Stomatology, Shandong University, Jinan, Shandong 250012, People’s Republic of China; 2Department of Oral and Maxillofacial Surgery, School of Stomatology, Shandong University, Jinan, Shandong 250012, People’s Republic of China; 3Department of Oral and Maxillofacial Surgery, Jinan Stomatological Hospital, Jinan, Shandong 250012, People’s Republic of China *These authors contributed equally to this work Objective: The focus of this meta-analysis was to assess the sedative effect and safety of intranasal dexmedetomidine (Dex) in mandibular third molar surgery.Methods: The PubMed/Medline, Web of Science, Cochrane Library, and China National Knowledge Infrastructure databases were searched for studies published until May 1, 2018. Eligible studies were restricted to randomized controlled trials (RCTs) and controlled clinical trials. The evaluation indicators mainly included the bispectral index, observer assessment of alertness/sedation scale, systolic blood pressure, and heart rate. Data for each period in the Dex and control groups were pooled to evaluate its sedative effect and safety.Results: Five RCTs met the inclusion criteria. This study included 363 patients: 158 patients received intranasal inhalation of Dex before surgery, and 158 patients were negative controls. The pooled results showed a good sedative effect during tooth extraction when intranasal inhalation of Dex was performed 30 minutes before third molar extraction (assessment of alertness/sedation, Dex vs control SMD -1.20, 95% CI -1.73 to -0.67, I2=0, P=0.95; bispectral index, Dex vs control SMD -11.68, 95% CI -19.49 to -3.87, I2=89%; P=0.0001), and parameters returned to normal within 90 minutes after inhalation. During the operation, blood pressure and heart rate decreased to some extent, but the decreases did not exceed 20% of the baseline, and all patients returned to normal conditions within 90 minutes after inhalation.Conclusion: Intranasal inhalation of Dex 30 minutes before third molar extraction can provide a good sedative effect, and large-sample multicenter RCTs are needed to evaluate the analgesic effect of Dex. Keywords: intranasal dexmedetomidine, sedation, mandibular third molar, meta-analysis